27=mm+6

Rewrite the equation as mm+6=27.

mm+6=27

Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.

m⋅7=(m+6)⋅2

Move 7 to the left of m.

7m=(m+6)⋅2

Simplify (m+6)⋅2.

Apply the distributive property.

7m=m⋅2+6⋅2

Simplify the expression.

Move 2 to the left of m.

7m=2⋅m+6⋅2

Multiply 6 by 2.

7m=2m+12

7m=2m+12

7m=2m+12

Move all terms containing m to the left side of the equation.

Subtract 2m from both sides of the equation.

7m-2m=12

Subtract 2m from 7m.

5m=12

5m=12

Divide each term by 5 and simplify.

Divide each term in 5m=12 by 5.

5m5=125

Cancel the common factor of 5.

Cancel the common factor.

5m5=125

Divide m by 1.

m=125

m=125

m=125

m=125

The result can be shown in multiple forms.

Exact Form:

m=125

Decimal Form:

m=2.4

Mixed Number Form:

m=225

Solve for m 2/7=m/(m+6)